Predicting the environmental and socio-economic impacts of displaced fishing effort from a hypothetical highly protected marine area, located in English inshore waters - Reeves, Laura A.; Hartley, Melanie; Stewart, James E.; Clark, Sarah; Parkhouse, Lauren; Vaughan, Duncan (Frontiers in Marine Science, 2025)
In response to the Benyon review the UK Government introduced three Highly Protected Marine Areas (HPMAs), adding to the 178 Marine protected areas (MPAs) already designated in English waters. All extractive, destructive and depositional activities are prohibited within HPMAs to promote ecosystem recovery. However, it is a requirement of the designation process to consider the socio-economic impacts of the placement of a HPMA. There are many marine sectors competing for space in English waters, therefore displacing all damaging or disturbing activities occurring within newly designated HPMAs could further exacerbate this conflict. One key marine sector that is vulnerable to displacement from HPMAs is commercial fishing. Although a template to assess displacement has been developed, this template has not yet been applied. Therefore, this study aims to bridge this gap; applying a full displacement assessment to a Hypothetical HPMA (HypHPMA, 25km2), located within English inshore waters. This study investigates the extent to which commercial fishing vessels use the HypHPMA and potential reductions in catch (kg) and gross revenue changes (£) resulting from their displacement following hypothetical designation, using the R package VMStools. In addition, the habitat type and sensitivity within the HypHPMA and surrounding areas were analysed to highlight sensitive areas now protected by the HypHPMA or surrounding areas that may be more sensitive to fishing displacement. Our method allows fine spatial and temporal scales of socioeconomic analysis which can identify fleet and individual vessel vulnerabilities to displacement, alongside environmental analyses which quantify interactions between fishing gear and specific sensitive habitats. This method has wider utility than assessing displacement from HPMAs – it can be used to assess displacement resulting from other spatial management measures that restrict fishing activity.